Design and fabrication of wet clothes’ spinning machine / Nadzirah Huda Ariuddin and Mohd Fadzli Ismail - Ariuddin, Nadzirah Huda; Ismail, Mohd Fadzli (School of Mechanical Engineering, 2023)
Squeezing wet clothes by hand after hand washing takes a lot of energy and time for some people. This project aims to address the problem of squeezing wet clothes by hand, which is time-consuming and demanding, especially for busy college students. The objective of this project is to design and fabricate semi-automated wet clothes’ spinning machine that can efficiently remove water from wet clothes, while being portable and easy to use. The machine was designed in Solidworks and fabricated using a plastic basket as drum, slotted angle bar as frame, polycarbonate sheets as its cover, DC motor, and power adaptor. The user simply loads the wet clothes into the basket, closes the lid, and turns on the machine using a switch, and the machine spins the basket to remove water from the clothes. Results showed that the machine successfully removed water from wet clothes, reducing the effort and time required to dry clothes. Overall, this wet clothes' spinning machine is a practical solution for the problem of squeezing wet clothes by hand and can save time and energy, making it a useful tool for college students.